Prognostic significance of systemic pan-immune-inflammation value in locally advanced cervical cancer - Yan, Shu; Gong, Xin; Liu, Rui; Jia, Xiaojing (Frontiers in Oncology, 2024)
ObjectiveThis study investigates the significance of systemic pan-immune inflammation value (PIV) prior to concurrent chemoradiotherapy (CCRT) in predicting the therapeutic efficacy as well as prognosis of patients with locally advanced cervical squamous cell carcinoma.MethodsA retrospective analysis was conducted on the clinical data of 847 patients with locally advanced cervical cancer (LACC) treated at the Second Hospital of Jilin University between 2016 and 2020. All patients underwent radical CCRT, including platinum-based sensitizing chemotherapy. The PIV was measured as given by: (platelet count × neutrophil count × monocyte count)/lymphocyte count. Logistic regression analysis was utilized to study the effect of PIV on therapeutic response in LACC patients and Kaplan–Meier survival together with Cox proportional hazard model to assess its impact on prognosis.ResultsWith the therapeutic effect as the endpoint, the optimal cutoff of PIV (356.0099) was signified via the receiver operating characteristics curve, and patients were grouped and compared based on this value. PIV was determined as an independent predictor of the therapeutic effect in CCRT for LACC (hazard ratio (HR) 1.696, 95% confidence interval (CI) 1.111–2.590). PIV was also an independent predictor of overall survival (OS) (HR 0.540, 95% CI 0.409–0.713, p<0.001) as well as disease-free survival (DFS) (HR 0.680, 95% CI 0.528–0.876, p=0.003). Compared to the low-PIV group, it was noted that individuals with a high PIV exhibited a poorer therapeutic effect and shorter OS and DFS.ConclusionPatients with LACC and high PIV had poorer therapeutic outcomes and shorter OS and DFS. Our results may provide PIV as a new prognostic biomarker for LACC, if future prospective studies with large patient numbers support our findings.